Investigation of the microstructures of iron based wrought Cr-Ni-Mo duplex alloy - Kuzucu, V; Ceylan, M; Aksoy, M; Aksoy, I; Kaplan, M (Elsevier Science Sa Lausanne, 1997)
Samples of duplex stainless steel, consisting of iron-based Cr-Ni-Mo ahoy containing some other elements undergoing various heat treatments after having been wrought at 1150 degrees C, have been investigated using X-ray diffraction, thermal analysis and metallographic techniques. It is determined that some intermetallic phases such as Laves, mu, G, mu, R, chi, and some carbide phases as such M23C6, M7C3, M6C may be found in these samples and that the ratio of carbide phases decreased in samples annealed at 950 degrees C. In samples cooled in liquid nitrogen, it is seen that some dissolving elements in the matrix have accumulated around the sigma phases and some precipitation phases have occurred. It is concluded that the use of annealing of this material at 950 degrees C affects the chemical, mechanical and other properties adversely. (C) 1997 Elsevier Science S.A.
Keywords: iron; duplex stainless steel; hot working